A secure and efficient time-bound hierarchical access control scheme for secure broadcasting. (2016) - Odelu, Vanga; Das, Ashok Kumar; Goswami, Adrijit
In a time-bound cryptographic key assignment scheme, distinct temporal keys for distinct time periods are assigned to the channels in order to encrypt and decrypt the channels for secure broadcasting. It has numerous applications including the Pay-TV systems. In this paper, we aim to propose a novel time-bound hierarchical access control scheme for secure broadcasting, in which each user needs to store a distinct and unique user's private key, and hence each user in a channel group can subscribe for an individual channel. Our scheme reduces significantly the implementation cost and also improves the computational performance along with extra features. Through the informal and formal security analysis, it is shown that our scheme is secure against various known attacks including the collusion attack. As a result, our scheme is more secure and efficient as compared to other related schemes in the literature.